Analisis Penerimaan Pajak Daerah Sebagai Pendorong Pertumbuhan Ekonomi Dan Dampaknya Dalam Belanja Daerah - Pohan, Erlina Sari; Nasrullah, Achmad; Juwenah, Juwenah (Universitas 17 Agustus 1945 Jakarta, 2022)
The purpose of this study was to determine the growth rate, revenue effectiveness, effectiveness of regional spending, contribution of local tax revenue to regional economic growth, contribution of local tax revenue to regional spending and the rate of economic growth in Cilegon based on GRDP at current prices. The research method used is a qualitative descriptive method with data and budget targets for PAD, regional taxes, expenditures and regional GRDP in 2014-2018. The results showed that the growth rate of local taxes in 2015 was 21.23%, in 2015 it was 4.84%, in 2017 it was 16.14% and in 2018 it was 5.85%. Effectiveness of Regional Taxes, the average level of effectiveness in 2014-2018 is 99.83% (effective). For the level of effectiveness of 2014-2018 Regional Expenditures which reached 80-90% (enough). The contribution of income to regional economic growth in 2014-2018 exceeds 100% (very good). The contribution of Regional Tax receipts to Regional Expenditures for 2014-2018 reached 20.10-30% (medium). The economic growth rate in 2015 was 4.17%, in 2016 it was 4.99%, in 2017 it was 5.46% and in 2018 it was 5.82%. Contributions in this research contribute ideas to the City Government of Cilegon and become a material for consideration in making decisions and policies for better development in the future.